First data on the structure of the vertebral column in Gobio and Romanogobio species (Actinopterygii, Cypriniformes, Gobionidae) from Ohrid Lake and the Vardar River basin - Arsovska, Julijana; Ristovska, Milica; Simonović, Predrag; Kostov, Vasil; Slavevska-Stamenkovič, Valentina (Pensoft Publishers, 2021)
The validity of four gudgeon species known for the ichthyofauna of North Macedonia has been a matter of different taxonomic disputes (except forGobio ohridanusKaraman, 1924). Recently, a restoration of the species status was proposed forGobio balcanicusDimovski et Grupče, 1977 andRomanogobio banarescui(Dimovski et Grupče, 1974). So far,Romanogobio stankoi(Karaman, 1974), has not been a part of any recent investigation and it is still considered as a junior synonym ofRomanogobio elimeius(Kattoulas, Stephanidis et Economidis, 1973) orR. banarescuidue to the lack of distinctive morphological characters. The osteological characters in the structure of the vertebral column, have significance to the systematics of the gudgeons, especially in elevation ofRomanogobioat the level of genus. To contribute to resolving the taxonomic status in these gudgeon species, the goal of this paper is to identify distinctive characters by presenting and analyzing the structure of their vertebral column. Samples were inspected from the fish collections in the Institute of Biology (G. ohridanus), the Institute of Animal Science (G. balcanicus), and the Macedonian Museum of Natural History (bothRomanogobiospecies). Fish samples were X-rayed as well as cleared and double-stained. Obtained data on the number of vertebrae were presented through the vertebral formula following Naseka (1996). Multiple Correspondence Analysis (MCA) was used to check the interrelation between taxa and the number of vertebrae in all units of the vertebral column.G. balcanicusis distinguished fromG. ohridanusmainly in the predorsal and preanal subregion (10 vs. 11 vertebrae and 1 vs. 0 vertebrae, respectively), whileR. stankoidistinguishes fromR. banarescuiby the number of vertebrae in the preanal and postanal subregion (2 vs. 4 vertebrae and 19 vs. 17 vertebrae, respectively). The structure of vertebral column offers distinctive morphological characters for the four gudgeon species from Ohird Lake and the Vardar River basin.
Keywords: 􏱮􏰄􏱜􏱗􏰛􏰙􏰕􏰁􏰟 􏰨􏱳􏱯 􏱤􏰕􏱤􏰚􏰃􏰁􏰔􏰁􏰟 􏰂􏰛􏰓􏰀􏰛􏰠􏰓􏱤􏰛􏰟 􏰂􏰛􏰓􏰀􏰛􏰠􏰓􏱤􏰚 􏰢􏰙􏰚􏰄􏰝􏰕􏰟 􏰂􏰛􏰓􏰀􏰛􏰠􏰓􏱤􏰚 􏱘􏰙􏰓􏰝􏰄􏰚􏱤